Efficiency of thermo–photocatalytic production of hydrogen from biomolecules: a multifaceted perspective. (16th September 2022) - Gómez-Cerezo, María Natividad; Barba-Nieto, Irene; Fernández-García, Marcos; Kubacka, Anna
Abstract : Measuring and interpreting the efficiency of a thermo–photocatalytic reaction is key in the quest to define synergy for chemical reactions taking place under dual thermo–photo excitation. Abstract : Measuring and interpreting the efficiency of a thermo–photocatalytic reaction is key in the quest to define synergy for chemical reactions taking place under dual thermo–photo excitation. The analysis of the efficiency parameter requires multiple facets of the problem to be taken into account, demanding a detailed study of the chemical, photon and global energy balances of the reaction. This manuscript discussed how to approach such a goal, starting from using mathematical frameworks for the measurement of the three mentioned facets of the efficiency parameter with the help of the corresponding excess functions and ending with the interpretation of synergy through an adequate physico-chemical investigation using modern operando spectroscopic and theoretical tools.